Edukasi Hidup Sehat Dimasa Pandemi Untuk Anak Sekolah Dasar - Nazmi, Annisa Nur; Indriani, Ninis (PPPM Stikes Banyuwangi, 2022)
Background: Implementing a healthy lifestyle is also very important, especially during a pandemic like this, maintaining health and body immunity is the main and most important thing to avoid the covid-19 virus, including school children. From an early age, children must be introduced to a sense of responsibility and a sense of caring for the environment and themselves, especially during a pandemic emergency where children are an age group that is vulnerable to infection. Purpose: from this community service is to improve the health status of elementary school residents, especially students. Method of community service uses education about covid-19, prevention of transmission of covid 19 and healthy living during a pandemic and how to wash hands properly as an effort to prevent transmission of Covid-19. Results: The community service activities were attended by 121 students, mostly 67% of the students were male. This community service activity increases the knowledge of students/partners related to the transmission and prevention of the covid 19 virus and improves a clean and healthy lifestyle for elementary school students. Conclusion: This community service activity is carried out by providing education related to the transmission and prevention of covid 19 which has a positive impact on partners, there is an increase in knowledge about covid 19 and an increase in correct hand washing skills as an effort to prevent the transmission of covid 19.